PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR DALAM PENGUKURAN KINERJA (Studi Kasus Pada RSUD dr. Wahidin Sudiro Husodo Kota Mojokerto) - ‘Ulya, Eva Choirul; Saraswati, Erwin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to measure the performance of RSUD dr. Wahidin Sudiro Husodo Mojokerto using the balanced scorecard method. There are four perspectives in a balanced scorecard measurement: financial perspective, customer perspective, internal business perspective, and learning and growth perspective. This research uses primary data by spreading questionnaires to patients and employees of RSUD dr. Wahidin Sudiro Husodo Mojokerto, and using secondary data including financial statements, the number of patients, and employee attendance data, during 2010 through 2013. Internal business perspective shows good result, customer perspective and financial perspective show quite good result, but learning and growth perspective shows below standard result. Seen from four perspectives of balanced scorecard method, over all performance of RSUD dr. Wahidin Sudiro Husodo Mojokerto is good enough. Keywords: general hospital, balanced scorecard